Physical and Chemical Properties Nata de Cascara on The Different Treatment of Fermentation’s Time with SCOBY (Symbiotic Culture of Bacteria and Yeast) - Bhakti Etza Setiani; Yasinta Azhar Sausan; Siti Susanti (Journal of Applied Food Technology, 2021)
Cascara, the dried outer pulp and skin of the coffee cherry is usually discarded as waste. However, there is a growing interest in reutilizing this coffee cherry by-product as a unique product. This study aims to determine the effect of fermentation time on the physical and chemical properties of Nata de Cascara Arabica with a SCOBY starter. The material used in this research was Arabica cascara coffee as the raw material for making kombucha. The research method was designed as a Completely Randomized Design (CRD) with fermentation time as the factor, conducted in five repetitions. Fermentation periods of 8, 12, 16, and 20 days were analyzed for various physical and chemical parameters, including SCOBY’s thickness, yield, color, moisture content, and crude fiber. The data on the results of physical and chemical properties were analyzed using Analysis of Variance (ANOVA) at a 95% confidence level. If differences were found, the Duncan test was applied. The results showed that longer fermentation times significantly affected (p<0.05) moisture content and color (Redness), while thickness, yield, color (lightness), and crude fiber content increased. The best treatment for making Nata de Cascara Arabica is fermentation for 20 days.